Ketika Aku dan Kamu Menjadi Kita: Dialog Misi Penginjilan Kristen dengan Dakwah Islam Menggunakan Pendekatan Teologi Interkultural dalam Konteks Indonesia - Daniel Syafaat Siahaan (Faculty of Theology Duta Wacana Christian University, 2017)
Abstract Evangelism and da'wah are two obligations or responsibilities of people, Christians and muslims. I wonder how long these two religions involved in a